USAID Bureau for Resilience and Food Security staff trained to use to the Kaleidoscope Model for Food Security Policy Change - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The Kaleidoscope Model is a tool that can be used by researchers, practitioners and donors to identify entry points for improving the likelihood of policy change. Since 2018, this tool is included in training materials for USAID's Bureau for Resilience and Food Security staff.